2008
DOI: 10.1007/s00114-008-0382-z
|View full text |Cite
|
Sign up to set email alerts
|

Male-biased predation of a cave fish by a giant water bug

Abstract: Male-biased predation has been described from several epigean species, and in many cases, intrinsic differences between the sexes (such as male ornaments) have been suggested as an explanation. Here we report on male-biased predation of a cave fish (Poecilia mexicana) by an aquatic insect (Belostoma sp.) in a Mexican sulfur cave. P. mexicana use aquatic surface respiration (ASR) to survive in their sulfidic, hypoxic habitat. We found that males typically exhibit more ASR activity than females, which leads to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 53 publications
1
34
0
Order By: Relevance
“…Using prey choice experiments under semi-natural conditions, we first experimentally confirmed the assumption that D. esakii prey on G. affinis, as previous studies found other belostomatines (including members of the genus Diplonychus) to include fish prey (Plath et al 2003(Plath et al , 2011Tobler et al 2007Tobler et al , 2008Tobler et al , 2013Hazarika and Goswami 2012). Having confirmed this assumption, (1) we then asked if a pattern of size-specific predation exists.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Using prey choice experiments under semi-natural conditions, we first experimentally confirmed the assumption that D. esakii prey on G. affinis, as previous studies found other belostomatines (including members of the genus Diplonychus) to include fish prey (Plath et al 2003(Plath et al , 2011Tobler et al 2007Tobler et al , 2008Tobler et al , 2013Hazarika and Goswami 2012). Having confirmed this assumption, (1) we then asked if a pattern of size-specific predation exists.…”
Section: Introductionsupporting
confidence: 59%
“…By contrast, a strong signal of male-biased predation was uncovered in a study on predation by B. cf. bakeri on P. mexicana in a hydrogen sulfide-rich cave (Tobler et al 2008). The authors reported on higher oxygen demands of male fish leading to more aquatic surface respiration under hypoxic conditions, thus exposing males to elevated levels of predation risk.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Belostoma have been shown to preferentially attack certain sizes and sexes of prey, and thus may exert strong selective pressures on prey species (Tobler et al , 2008b. Similarly, immigrants to cave and surface habitats could be attacked selectively, as cave and surface fish have diverged in sensory structures (Parzefall 2001).…”
Section: Introductionmentioning
confidence: 99%